Entre nature et culture - Manola Antonioli (Appareil)
Based on Vilém Flusser’s Essays on Nature and Culture, the article examines the complex links between nature and culture that the author brings to bear in his thinking. In his essays, Flusser examines paths as a hybridization between the conscious project of human culture, the “project” traced by animals and the (allegedly “natural”) dimension of landscapes. There are also reflections on animals (cows and birds) and on the writing scene, which combines the “natural” dimension of fingers with writing machines (from pen to typewriter and then to computer). In Les gestes, the act of planting becomes the starting point for a reflection on agriculture and ecology, which continues in the unpublished text entitled “‘Ecological’ Considerations”. Finally, the new relationship between the human and animal worlds is discussed in the book on Vampyroteuthis infernalis, the result of a long collaboration between Vilém Flusser and the artist Louis Bec.